2018
DOI: 10.1016/j.ymgme.2017.12.321
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease: Multi-disciplinary evaluation after 15 years of treatment with agalsidase beta

Abstract: Fabry disease is an X linked disorder of metabolism due to deficient a-galactosidase A activity. Enzyme replacement therapy (ERT) with agalsidase Beta was approved by EMA in FDA in 2003. Patients and methods: Six patients were enrolled. Baseline data was measured for renal, cardiac, and cerebrovascular functioning. We compared baseline quality of life scales with the current results. These parameters were assessed during the 10 years of follow-up period.Results: Before ERT four patients showed normal eGFR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…6 Department of Nephrology, Royal Melbourne Hospital, Parkville, VIC, Australia. 7 Department of Medicine, University of Melbourne -Parkville Campus, Parkville, VIC, Australia. 8 Department of Endocrinology and Clinical Nutrition, University Hospital Zurich and University of Zurich, Zurich, Switzerland.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Department of Nephrology, Royal Melbourne Hospital, Parkville, VIC, Australia. 7 Department of Medicine, University of Melbourne -Parkville Campus, Parkville, VIC, Australia. 8 Department of Endocrinology and Clinical Nutrition, University Hospital Zurich and University of Zurich, Zurich, Switzerland.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Judging prognosis and, thus, when to initiate FD-specific treatment is a clinical challenge complicated by evidence that the best outcomes are associated with early treatment initiation. Long-term studies of patients with FD who initiated disease-specific therapy at an early stage have shown that it has a stabilizing effect on renal and cardiac parameters [6,7]. Studies in vitro have implicated LysoGb3 in the formation of fibrosis and, in particular, the presence of renal or cardiac fibrosis on biopsy seems to mark a pivotal stage in FD after which disease-specific therapy becomes less effective [8].…”
Section: Introductionmentioning
confidence: 99%